Forensic Accounting Practices and Fraud Detection: Insights from the Nepali Banking Sector - Subedi, Purushottam; Neupane, Sarmila (NPRC Journal of Multidisciplinary Research, 2024)
This study examines the role of forensic accounting in fraud detection within Nepali banks, focusing on practices like control systems reliance, litigation hotlines, whistleblower hotlines, and digital fraud reviews to assess their impact on fraud prevention. A quantitative, descriptive, and causal-comparative approach was used to collect primary data from 385 employees of Nepali banks through a structured questionnaire. Descriptive statistics revealed moderate implementation and positive perceptions of forensic accounting practices, with control systems reliance showing the highest level of implementation. Correlation analysis confirmed strong positive relationships among all variables. Regression analysis indicated that factors such as sustainable governance systems, ethical philosophy, and digital fraud reviews significantly impacted fraud detection. The model explained approximately 57.2% of the variance in fraud detection, emphasizing the importance of forensic accounting in strengthening fraud prevention in Nepali banks. Forensic accounting plays a vital role in improving fraud detection within the Nepali banking sector. To enhance fraud detection capabilities, it is recommended that banks prioritize these key forensic accounting measures and integrate them more effectively into their operational frameworks.